Поліморфізм молекулярного маркера гена Н1, асоційованого зі стійкістю до золотистої нематоди (Globodera rostochiensis), серед сортів картоплі (Solanum tuberosum ssp. tuberosum) української та світової селекції - Карелов, А.В.; Пилипенко, Л.А.; Козуб, Н.О.; Бондус, Р.О.; Філенко, О.Л.; Созінов, І.О.; Блюм, Я.Б.; Созінов, О.О. (Фактори експериментальної еволюції організмів, 2013)
Aim. The aim of our investigation was determination of allelic condition of resistance gene H1 against the pathotypes Ro1 and Ro4 of golden potato cyst nematode among the Ukrainian and world potato cultivars. Methods. The allelic condition of the TG689 marker was determined by PCR with DNA samples isolated from tubers of potato. Results. Among 78 potato cultivars analyzed the allele of marker associated with the H1-type resistance was found in 74 % of Ukrainian and 90 % foreign ones, although some of those cultivars proved to be susceptible to the golden potato nematode in the field. Conclusions. The obtained data confirm the presence of H1-resistance against golden nematode pathotypes Ro1 and Ro4 among the Ukrainian potato cultivars.